Radical resection of primary leiomyosarcoma of inferior vena cava - Mohamad I.S.; Nadarajan S.; Zuhdi Z.; Idris A.; Othman H.; Ariffin, AC; Jarmin R. (Faculty of Medicine and Health Sciences, 2024)
Indexed by SCOPUS